Recent Advances in Understanding the Structural and Functional Evolution of FtsH Proteases - Yi, Lanbo; Liu, Bin; Nixon, Peter J.; Yu, Jianfeng; Chen, Feng (Frontiers in Plant Science, 2022)
The FtsH family of proteases are membrane-anchored, ATP-dependent, zinc metalloproteases. They are universally present in prokaryotes and the mitochondria and chloroplasts of eukaryotic cells. Most bacteria bear a single ftsH gene that produces hexameric homocomplexes with diverse house-keeping roles. However, in mitochondria, chloroplasts and cyanobacteria, multiple FtsH homologues form homo- and heterocomplexes with specialised functions in maintaining photosynthesis and respiration. The diversification of FtsH homologues combined with selective pairing of FtsH isomers is a versatile strategy to enable functional adaptation. In this article we summarise recent progress in understanding the evolution, structure and function of FtsH proteases with a focus on the role of FtsH in photosynthesis and respiration.